Kepemimpinan Pendidikan: Tinjauan terhadap Teori Sifat dan Tingkah-laku - Muh. Hizbul Muflihin (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
The substance of education is learning activity. The key of education successfulness is correlation and interaction between teacher and headmaster as top level leader at school. The ability or competence of school leader (headmaster) to develop teacher spirit or other employee is depending on character and ways shown to them. Its mean that good manner and how to treat other team-member has significant effect to his success to implement leadership at school. Education leader, at every level—headmaster, vice, teacher or other official—must able to play role as EMASLIM; namely educator, manager, administrator, supervisor, leader, innovator, and motivator.